Studies of magneto-tunneling into donor states and of the breakdown of the quantum Hall effect - Dickinson, Laurie Alan (2004)
This thesis describes an experimental investigation and analysis of two topical problems in condensed matter physics: 1.) the effect of a magnetic field on quantum states of an electron bound to a shallow donor impurity in a quantum well heterostructure and 2.) the breakdown of the quasi-dissipationless state of the integer quantum Hall effect. Two introductory chapters describe important material parameters and the experimental equipment and techniques used. Magneto-tunneling spectroscopy (MTS) is used to probe the spatial form of the eigenfunction of electrons bound in the ground state of a shallow Si-donor impurities in a GaAs/(A1Ga)As quantum well. An in-plane magnetic field, B[subscript] |, acts to tune the k-vector of the tunnelling electron through the effect of the Lorentz force. The variation with B [subscript] | of the tunnel current through the donor ground state provides a map of the Fourier transform, |ψ(k)| [superscript]2, of the probability density of the ground state donor wavefunction in real space. By applying a strong magnetic field component, B [subscript] ||, parallel to the direction of tunnel current, it is possible to magneto-compress the donor function in real space. The magneto-compression is investigated using MTS and the data are analysed in terms of a simple model, which is critically discussed.